2000
DOI: 10.1152/physiolgenomics.2000.2.1.21
|View full text |Cite
|
Sign up to set email alerts
|

nNOS and eNOS modulate cGMP formation and vascular response in contracting fast-twitch skeletal muscle

Abstract: Nitric oxide (NO) from Ca(2+)-dependent neuronal nitric oxide synthase (nNOS) in skeletal muscle fibers may modulate vascular tone by a cGMP-dependent pathway similar to NO derived from NOS in endothelial cells (eNOS). In isolated fast-twitch extensor digitorum longus (EDL) muscles from control mice, cGMP formation increased approximately 166% with electrical stimulation (30 Hz, 15 s). cGMP levels were not altered in slow-twitch soleus muscles. The NOS inhibitor N(omega)-nitro-l-arginine abolished the contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 30 publications
7
165
1
2
Order By: Relevance
“…Such a positive effect of NO has also been found in insulin-resistant muscle cells derived from individuals with type 2 diabetes [21]. In addition, our observations, as those of several other groups, support the view that NO controls glucose transport via insulin-independent signalling pathways [48,49], including activation of cGMP-dependent protein kinase [50,51] and AMP-activated protein kinase-α1 [48,52]. Concerning the possible mechanisms involved, we found that restoration of endogenous nNOS in insulin-resistant muscle cells greatly improved translocation of GLUT4 at the plasma membrane in the presence of insulin, but not in basal conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Such a positive effect of NO has also been found in insulin-resistant muscle cells derived from individuals with type 2 diabetes [21]. In addition, our observations, as those of several other groups, support the view that NO controls glucose transport via insulin-independent signalling pathways [48,49], including activation of cGMP-dependent protein kinase [50,51] and AMP-activated protein kinase-α1 [48,52]. Concerning the possible mechanisms involved, we found that restoration of endogenous nNOS in insulin-resistant muscle cells greatly improved translocation of GLUT4 at the plasma membrane in the presence of insulin, but not in basal conditions.…”
Section: Discussionsupporting
confidence: 89%
“…This small absolute increase in COX activity was completely reversed by voluntary activity. The relative resistance of glycolytic muscle to eNOS deficiency may be explained by lower eNOS expression (30,34) and relatively lower sensitivity of skeletal glycolytic fiber blood perfusion to NO production (38).…”
Section: Discussionmentioning
confidence: 99%
“…Both muscle contraction [42] and SNP [18,42] increase cGMP formation. Furthermore pharmacological manipulation of both soluble guanylate cyclase and cGMP modulates the effect of SNP on glucose uptake [18,43].…”
Section: Signalling Pathwaysmentioning
confidence: 96%